Impact of salt crystal size on in-mouth delivery of sodium and saltiness perception from snack foods - Rama, Ruben; Chiu, Natalie; Da Silva, Margarida Carvalho; Hewson, Louise; Hort, Joanne; Fisk, Ian D. (Wiley, 2013)
Fried, sliced potato crisps were flavored with sodium chloride of varying size fractions to investigate the impact of salt crystal size on the delivery rate of sodium to the tongue and resultant saltiness, measured over 65 s with a defined chew protocol (three chews, then holding the bolus in the mouth without swallowing). Salt crystal size impacted upon the delivery rate and perceived saltiness. The smallest crystal size fraction dissolved and diffused throughout the mouth to the tongue saliva faster than the medium and the largest ones; the smallest crystal size fraction also had the highest maximum concentration and greatest total sodium. These results correlated well with the sensory perceived saltiness, where the smallest crystal size fraction resulted in the fastest Tmax, highest maximum saltiness intensity and maximum total saltiness. The different delivery rates can be explained by differential dissolution kinetics and enhanced mass transfer of sodium across the saliva.